2019
DOI: 10.1177/0018726718817818
|View full text |Cite
|
Sign up to set email alerts
|

Micro-political processes in a multinational corporation subsidiary: A postcolonial reading of restructuring in a sales department

Abstract: What shapes micro-political contest in the subsidiary of a multinational corporation? We use observational and interview data from a Pakistani subsidiary of a global company to address this question. We trace debate surrounding the entry of modern (self-service) retail through multiple voices. Following postcolonial theory, we show how top management create a narrative that combines the progressiveness of modern retail with the locally salient discourse of izzat/honour. This hybrid narrative defines the terrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…In conclusion, then, this paper has built on existing efforts to bring into focus the connections between colonialism and international development management (e.g., Cooke, 2003;Dar, 2017;Kenny, 2008), drawing on empirical insights and the analytic of coloniality to reveal how inequality between local and foreign development workers is rooted in and sustained by onto-epistemic difference. Further, by demonstrating how American management rationalities are ingrained in formal and informal evaluation and appraisal mechanisms, this paper sheds light on the colonial power dynamics of international organizations, contributing to critical perspectives on international management and organization (Boussebaa & Morgan, 2014;Hopkinson & Aman, 2019). Finally, by foregrounding coloniality-with race as its central organizing feature-this paper has aimed to challenge decontextualized or silent stances around race in organization and development studies, shedding light on the onto-epistemic bases of difference that allow inequality in organizations to endure (Crewe & Fernando, 2006;Kothari, 2006;Nkomo, 1992).…”
Section: Concluding Discussion: Foreign-local Inequality and The Colo...mentioning
confidence: 93%
“…In conclusion, then, this paper has built on existing efforts to bring into focus the connections between colonialism and international development management (e.g., Cooke, 2003;Dar, 2017;Kenny, 2008), drawing on empirical insights and the analytic of coloniality to reveal how inequality between local and foreign development workers is rooted in and sustained by onto-epistemic difference. Further, by demonstrating how American management rationalities are ingrained in formal and informal evaluation and appraisal mechanisms, this paper sheds light on the colonial power dynamics of international organizations, contributing to critical perspectives on international management and organization (Boussebaa & Morgan, 2014;Hopkinson & Aman, 2019). Finally, by foregrounding coloniality-with race as its central organizing feature-this paper has aimed to challenge decontextualized or silent stances around race in organization and development studies, shedding light on the onto-epistemic bases of difference that allow inequality in organizations to endure (Crewe & Fernando, 2006;Kothari, 2006;Nkomo, 1992).…”
Section: Concluding Discussion: Foreign-local Inequality and The Colo...mentioning
confidence: 93%
“…Moreover, a number of studies have integrated the micro-political perspective into their analyses of employment relationships. These studies have explored the transfer of practices in multinational companies (Bélanger et al, 2013; Ferner et al, 2011); the relationship between trade unions and management (Bourguignon et al, 2020; Helfen et al, 2017); the weight of institutions (Ferner et al, 2005; Geppert et al, 2015) and, more recently, the influence of geopolitical factors (Hopkinson and Aman, 2019). In particular, these works have shown that to understand the relationships between trade unions and management, they cannot be conceptualised as relations between two homogeneous sides; the complexity of power relations in the workplace needs to be considered.…”
Section: The Micro-politics Of Gender Equality Bargainingmentioning
confidence: 99%
“…Ulus (2015) shows how neocolonial dynamics and power relations are reproduced daily in the Indian context, and Dar (2018) illustrates how such power relations are sustained by using the English language. Hopkinson and Aman (2019) offer an analysis of micro-political contests and struggles in Pakistan in relation to MNCs’ actions, while Boussebaa et al (2012, p. 480) explore ‘inter-office conflicts’ in management consultancies where western consultants pre-structure their world as a ‘postcolonial hierarchy’. As such, MNCs are among the most significant carriers of neocolonialism worldwide (Boussebaa et al, 2014; Boussebaa & Morgan, 2014; Garfolo & L’Huillier, 2014; Petras & Veltmeyer, 2001).…”
Section: From Ethnocentrism To Neocolonialism In Mnc Researchmentioning
confidence: 99%
“…Due to the apparent pressures on top management to devise and promote an enduring organizational identity (Anteby & Molnár, 2012), they sustain traditional neocolonial identity work in the face of challenges. However, it becomes an object of tensions and struggles in the complex MNC organization (Hopkinson & Aman, 2019), where the more contemporary version of neocolonialism is effectively silenced, and the HQ ingroup are reluctant to give up their power and privileged position.…”
Section: Organizational Identity Work In Dancommentioning
confidence: 99%
See 1 more Smart Citation